Evaluación de la calidad del agua del río Malacatos en el tramo Dos Puentes – La Tebaida, mediante modelación matemática para periodos de estiaje - Cordova Romero, Alex Vinicio (2024)
Due to increasing urbanization and productive economic activities, the deterioration of water quality is becoming more relevant worldwide. The purpose of this study was to evaluate the water quality of the Malacatos river in the segment between the Dos Puentes sector and the La Tebaida neighborhood using mathematical modeling. The physicochemical parameters of 19 water discharges and 4 control points were analyzed through three samplings during 2 months (December 2022 and January 2023). Dissolved oxygen (DO), biochemical oxygen demand (BOD) and ammonia nitrogen (NH4 + ) were modeled based on the general pollutant transport equation, solved by the Euler method, and the model obtained was calibrated. Discharges showed high contamination, exceeding the 200 mg/l COD and 100 mg/l BOD proposed by Ecuadorian regulations as the maximum permissible limits for discharges into freshwater, especially at points AP12, AP15, AP16 and AP17. The mathematical model showed that these discharges significantly impact the receiving body, generating an increase in contamination starting at kilometer 5.8, which causes the BOD MPLS to be exceeded in the main channel. The most influential discharge was at AP17, which produced a 64% increase in BOD, 47% in NH4 + and a 4.87% decrease in DO. In the calibration process, the model was adjusted with errors lower than 10% for each of the three modeled parameters; therefore, it is a suitable representation of water quality. The validation process was not carried out due to the lack of sufficient data.